2010
DOI: 10.1371/journal.pone.0010405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Pioglitazone Treatment on Peripheral and Central Markers of Aging

Abstract: BackgroundThiazolidinediones (TZDs) activate peroxisome proliferator-activated receptor gamma (PPARγ) and are used clinically to help restore peripheral insulin sensitivity in Type 2 diabetes (T2DM). Interestingly, long-term treatment of mouse models of Alzheimer's disease (AD) with TZDs also has been shown to reduce several well-established brain biomarkers of AD including inflammation, oxidative stress and Aβ accumulation. While TZD's actions in AD models help to elucidate the mechanisms underlying their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 128 publications
(176 reference statements)
9
39
0
Order By: Relevance
“…Consistent with clinical results, we observed that pioglitazone significantly increased the body weights of db/db mice, while G004 and glimepiride showed no difference (Desouza et al 2007;Blalock et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with clinical results, we observed that pioglitazone significantly increased the body weights of db/db mice, while G004 and glimepiride showed no difference (Desouza et al 2007;Blalock et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…MWM procedures were similar to the procedures previously described (96). Briefly, animals were trained to find a submerged platform in a pool of water (days 1-3).…”
Section: Methodsmentioning
confidence: 99%
“…1). Hippocampal slices were obtained, and LTP was recorded as previously described (96). I/O relationships were examined by recording fEPSPs in the CA1 region resulting from stimuli of increasing intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen samples were thawed immediately before analysis and then maintained on ice throughout the assay setup. Briefly, according to procedures recommended by the manufacturers and previously described (Blalock et al 2010), all plasma samples were diluted 1:5 in sample diluent and then incubated in duplicate overnight with capture beads specific to TNF-a,IL-6 and IL-10. The beads were subsequently washed and incubated for 2 h with a biotin-conjugated detection antibody and then for 30 min with streptavidin-phycoerythrin.…”
Section: Cardiac Hemodynamic Assessmentmentioning
confidence: 99%